(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article discusses the essence of cultural tourism, its role in the national economy, its impact on the development of society, and the prospects for the development of this sector in Uzbekistan. The importance of cultural tourism is analyzed from the point of view of preserving historical heritage, promoting national values, as well as contributing to economic growth.